Two-stage versus single-stage anaerobic co-digestion on methane synthesis: Energy prospects and microbial community - Devens, Kauanna Uyara; Ribeiro, Alexandre Rodrigues; Camargo, Franciele Pereira [UNESP]; Sakamoto, Isabel Kimiko; Varesche, Maria Bernadete Amâncio; Silva, Edson Luiz (Elsevier, 2025)
Cassava processing wastewater (CW), a byproduct generated during cassava processing activities, and glycerol (Gly), a byproduct of biodiesel production processes, have a high concentration of organic matter and digestibility, which provides them with great potential for hydrogen (H2) and methane (CH4) generation. This study evaluated the co-digestion of cassava wastewater and glycerol in a single-stage versus two-stage process using a fluidized bed reactor (AFBR), i.e., a mesophilic acidogenic reactor (MAR) + a sequential mesophilic reactor (SMR) and a mesophilic methanogenic reactor (MMR), operated at mesophilic temperature (30°C). Thus, the effect of increasing the organic matter concentration of 1–12.5 g [chemical oxygen demand] COD.L−1 (50 %:50 % on a COD basis) on CH4 production was verified. Co-digestion consistently yielded methane production in both single and two-stage processes. The two-stage process stood out as the single stage, providing a maximum CH4 Yield (MY) of 341.10 mL CH4. gCOD−1cons and CH4 production rate (MPR) of 168.23 mL of CH4.L−1.h−1, respectively. Regarding the microbial community, the methanogens Methanobacterium and Methanobrevibacter prevailed. Moreover, the two-stage and single-stage presented energy potentials of 161.23 kJ.d−1 and 54.26 kJ.d−1, in that order. Upon comparative analysis of the performance between two-stage and single-stage methanogenic reactors, it becomes apparent that the co-digestion of CW and Gly in a two-stage configuration exhibited enhancements over the single-stage.
Keywords: Anaerobic fluidized bed reactor; Energy potential; Glycerin; Methanobacterium; Tapioca starch wastewater